2018
DOI: 10.3892/ol.2018.9182
|View full text |Cite
|
Sign up to set email alerts
|

Toll‑like receptor agonist rMBP‑NAP enhances antitumor cytokines production and CTL activity of peripheral blood mononuclear cells from patients with lung cancer

Abstract: Toll-like receptor (TLR) agonists are known for their ability to inhibit tumor progression via enhancing antitumor cytokines production and cytotoxic T lymphocyte (CTL) activity. Recombinant Helicobacter pylori neutrophil-activating protein fused with maltose-binding protein (rMBP-NAP) has been reported as a novel TLR agonist for antitumor treatment in murine models. The present study aimed to determine the potential and efficacy of the rMBP-NAP for antitumor treatment prior to further clinical trials. The rMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Cancer immunotherapy has rapidly advanced in recent years [ 21 ]. The main goal of cancer immunotherapy is to activate passive or active immunity to target tumors and combat growing malignancies [ 22 ]. Biologic agents such as antibodies, checkpoint inhibitors, and cytokines are a few of the many that comprise cancer immunotherapy [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer immunotherapy has rapidly advanced in recent years [ 21 ]. The main goal of cancer immunotherapy is to activate passive or active immunity to target tumors and combat growing malignancies [ 22 ]. Biologic agents such as antibodies, checkpoint inhibitors, and cytokines are a few of the many that comprise cancer immunotherapy [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cancer immunity cycle refers to the cyclic process during which neoantigens produced by cancer cells are released after cell death, captured, and then presented to T cells by antigen-presenting cells, activating effector T cells [ 25 ]. Effector T cells then traffic and infiltrate tumor tissue, where they kill cancer cells with the same tumor antigens, causing more antigen release [ 22 ]. Several studies have revealed that IFN signaling plays a critical role in the success of cancer therapy strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, NAP is currently being studied in tumor therapy given its ability to induce TLR2 transcripts and promote peripheral blood mononuclear cells of cancer patients to secrete IFN-γ and IL-12. [49][50][51][52][53] Once TLR2 signaling is activated, the bridging protein MYD88 activates the downstream factors NF-κB and transcription activator protein 1 (AP-1) to secrete cytokines such as IL-12. 54 Additionally, the transcriptional regulator c-JUN is an important element of the JAK/STAT pathway and a component of AP-1.…”
Section: Discussionmentioning
confidence: 99%
“…This induces antitumor effects through a TLR-2-dependent mechanism in subcutaneous hepatoma and sarcoma mice model ( 156 ). rMBP-NAP can significantly increase peripheral blood mononuclear cells (PBMCs) that secrete IFN-γ, and prominently increases the cytotoxic activity of PBMCs derived from lung cancer patients ( 157 ). Treatment with rMBP-NAP restricts the progression of metastatic lung cancer in mice model by triggering antitumor immunity ( 158 ).…”
Section: Effects Of H Pylori On Tumor Immunotherap...mentioning
confidence: 99%